Bond Graph Modeling and Simulation of Hybrid Piezo-Flexural-Hydraulic Actuator - Rudraksha Kelkar; Mohith Santhya; Mithun Kanchan; Omkar S. Powar (Engineering Proceedings)
In this study, a hybrid piezo-flexural-hydraulic actuator is modeled and simulated using bond graph methodology. The hybrid actuator comprises piezoelectric stack actuator, mechanical flexural amplifier, and hydraulic piston actuator. The piezoelectric stack actuator produces electrically controllable displacement. This displacement is amplified by a cascading combination of flexural amplifier and hydraulic actuator. A domain-independent bond graph model for the proposed hybrid actuator is developed. Using this bond graph, a mathematical model and a state space representation for the hybrid actuator are derived. The bond graph model is simulated using a 20-sim bond graph simulation software. The results of the simulation provide displacement characteristics and sensitivity analysis for each component and the hybrid actuator as a whole. The study plays a significant role in understanding the dynamic behavior of a multi-domain system using the bond graph methodology.